Developing Road Infrastructure Route Planning: Increasing Feasibility of Toll Road Project - Berawi, Mohammed Ali; Zagloel, Teuku Yuri; Miraj, Perdana; Berawi, Abdur Rohim Boy; Titaheluw, Wellsi; Karim, Saipol Bari Bin Abd (UI Scholars Hub, 2016)
Indonesian government attempts to improve connectivity and to increase regional activities in Sumatera Island through the development of Trans Sumatera Toll Road (TSTR). However, despite its benefits to local economic development in Sumatera, the project shows low feasibility due to a low amount of investment. It can be attributed from the lack of planning in the initial phase to produce a comprehensive route that considers the various potentials of the regions. Thus, this research aims to investigate alternative route planning of Trans Sumatera Toll Road particularly in this paper for Central Sumatera by studying Gross Regional Domestic Product (GRDP), population and other significant factors. This research exposes cities and districts in Riau, West Sumatera, and Jambi which potentially contribute to the regional economy. Each selected towns and districts will be integrated with the intermodal system and connected to other functions to establish the Trans Sumatera Toll Road project in Central Sumatera. Compared to existing estimation of investment from public records, this alternative route has generated a competitive cost of investment which is estimated around 118,053,400,074,696 rupiahs. The research findings are expected to become the basis to improve other similar infrastructure toll road project development.